2014
DOI: 10.3109/10717544.2014.930761
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Preparation and characterization of novel lipid nanocapsules of ropivacaine for transdermal delivery

Abstract: Ropivacaine, a novel long-acting local anesthetic, has been proved to own superior advantage. However, the application form used in clinic, ropivacaine hydrochloride (Naropin Injection), which should be administed intravenously, is causing poor patient convenience. The purpose of this study was to formulate ropivacaine (RPV) in lipid nanocapsules (LNCs) and character the potential of LNCs in delivering RPV transdermally to exploit novel external preparation. The RPV-LNCs were successfully prepared by phase inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…All kinds of SLN and NLC suspensions prepared above were centrifuged at 10,000 rpm for 10 min and the supernatant was discarded. 14 , 25 , 26 The pellet was washed with Milli-Q water for three times. Mannitol (5.0%, w/v) was added as a cryoprotectant for the freeze-drying process.…”
Section: Methodsmentioning
confidence: 99%
“…All kinds of SLN and NLC suspensions prepared above were centrifuged at 10,000 rpm for 10 min and the supernatant was discarded. 14 , 25 , 26 The pellet was washed with Milli-Q water for three times. Mannitol (5.0%, w/v) was added as a cryoprotectant for the freeze-drying process.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas, various clinical studies indicated that RVC was rapidly cleared from the injection site and showed short efficacy of the severity of pain (approximately 2 h postoperatively) 8. Moreover, intravenous administration brings poor patient convenience and other toxicities such as arrhythmia 9,10. These clinical results have prompted that it was critical to the development of appropriate delivery systems and different administration routes that circumvent the aforementioned problem.…”
Section: Introductionmentioning
confidence: 99%
“…The results of HE studies indicated that the TPL-NPs could permeate into skin by changing SC structure. Both the interactions between mixed surfactants (Tween 80 and Transcutol HP) and skin and lipid exchange between lecithin and SC could increase the skin intercellular space and loosen SC dense structure [ 37 ]. Besides, TPL-NPs could inhibit or prevent evaporation, which could improve skin moisture and hydration [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%